MAKTABGACHA TARBIYA YOSHIDA RIVOJLANISHNING PSIXOLOGIK VA IJTIMOIY SHART-SHAROITLARI - Saytbekova, S.; Smetova, G. (SCIENCE and SOCIETY, 2022)
This article discusses the psychological and social conditions of the characteristics of the cognitive processes of a child at preschool age, the formation and development of children through the impact of various types of communication.